2006
DOI: 10.1089/acm.2006.12.881
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Center, Double-Blinded, Randomized Controlled Study to Evaluate the Relative Efficacy of Sublingual and Oral Vitamin B-Complex Administration in Reducing Total Serum Homocysteine Levels

Abstract: There was no statistically significant difference in serum tHcy concentrations between SL and PO groups either before or after treatment, substantiating the idea that there is no difference in efficacy between the two methods of vitamin complex delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Cyanocobalamin is the most economical—and historically the most used form—rendering it suitable for safe daily use [45]. There were no apparent substantial differences between the absorption of sublingual and oral forms [152,206]. However, oral dissolution could be critical in the secretion of the salivary R-binder and its subsequent bond.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanocobalamin is the most economical—and historically the most used form—rendering it suitable for safe daily use [45]. There were no apparent substantial differences between the absorption of sublingual and oral forms [152,206]. However, oral dissolution could be critical in the secretion of the salivary R-binder and its subsequent bond.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to oral dietary supplements, vitamin B12 is available in sublingual preparations as tablets or lozenges. These preparations are frequently marketed as having superior bioavailability 18,19 . Vitamin B12, in the form of cyanocobalamin and occasionally hydroxocobalamin, can be administered parenterally as a prescription medication, usually by intramuscular injection 17 .…”
Section: Resultsmentioning
confidence: 99%
“…One study found that small doses of vitamin B 12 in the range of 0.1–0.5 µg resulted in absorption ranging between 52% and 97%; doses of 1 µg and 5 µg resulted in mean absorption of 56% and 28%, respectively, while higher doses had even lower absorption, with 10 µg and 50 µg doses resulting in 16% and 3%, respectively, being absorbed 17 . While sublingual supplements are often promoted as being more efficiently absorbed, there is no evidence to show that this form of supplement is superior to regular oral vitamin B 12 44 . Vitamin B 12 supplements are not made from animal‐based products and are suitable for inclusion in a vegan diet.…”
Section: Vitamin B12 In the Vegetarian Dietmentioning
confidence: 99%